Factor VII and Fibrinogen Levels as Risk Factors for Venous Thrombosis - Koster, T; Rosendaal, F R; Reitsma, P H; Velden, P A van der; Briët, E; Vandenbroucke, J P (Thrombosis and Haemostasis, 1994)
The plasma levels of coagulation factor VII and fibrinogen are well known risk factors for arterial thrombosis. We tested the hypothesis that this association also exists for venous thrombosis. Additionally, MspI and Haelll polymorphisms in the factor VII and fibrinogen genes have recently been reported to be associated with the concentration of both proteins in the plasma. However, no conclusion could be drawn with respect to an increase or decrease in thrombosis risk. We undertook a population-based case-control study, in which 199 patients with a first, objectively confirmed episode of deep vein thrombosis, aged less than 70, and without a known malignant disorder were compared to 199 age-and sex-matched healthy controls, to evaluate the clinical importance of these reported findings.For fibrinogen we found a positive level-related association between the plasma fibrinogen level and thrombotic risk. Subjects with a plasma fibrinogen greater than 5 g/1 had an almost 4-fold increase of thrombosis risk. The frequencies of the different Haelll genotypes were out of balance only for the thrombosis patients, with a deficit of the H1H2 genotype. Possession of an H1H2 genotype was associated with a 40% reduction in thrombosis risk.For factor VII, neither the plasma level nor the MspI genotypes were related to deep vein thrombosis, although possession of a M2 allele was clearly associated with significantly lower factor VII levels. The frequencies of the Mspl-genotypes were the same for patients and control subjects and, exhibited Hardy-Weinberg equilibrium.Our results support that plasma fibrinogen, a determinant of arterial thrombosis is also a risk factor for venous thrombosis, while factor VII plasma concentration is unrelated to deep vein thrombosis, which is supported by the data from the DNA analysis of polymorphisms.